El descubrimiento de América en la última hora del mundo: la hermenéutica franciscana - Miguel Ángel Segundo Guzmán (Nuevo mundo - Mundos Nuevos, 2012)
The apocalyptic interpretation made by the Franciscans in the sixteenth century in relation to the discovery of America is the topic of this paper. The first twelve to arrive at New World were intellectual heirs of a long eschatological tradition, which gave a characteristic tone to the evangelization of America. At the dawn of modernity, utopian thought it possible to generate strategies of appropriation of space, but also was the basis to carve a new history, one that narrate the triumphs of faith in the context of the natural expansion of Christianity over a hidden land and dominated by Satan.